Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300500
|View full text |Cite
|
Sign up to set email alerts
|

Managing Messes in Computational Notebooks

Abstract: Data analysts use computational notebooks to write code for analyzing and visualizing data. Notebooks help analysts iteratively write analysis code by letting them interleave code with output, and selectively execute cells. However, as analysis progresses, analysts leave behind old code and outputs, and overwrite important code, producing cluttered and inconsistent notebooks. This paper introduces code gathering tools, extensions to computational notebooks that help analysts fnd, clean, recover, and compare ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 32 publications
(36 reference statements)
0
85
0
2
Order By: Relevance
“…Woodbury et al [44] define alternatives as "structurally different solutions to a design," while variations are "design solutions with identical model structure, but having different values assigned to parameters." Recent studies on data scientists' work practices have found that they write alternative versions of exploratory code [2,16,24,36] or use multiple alternative models, typically generated by different classes of 1 machine-learning algorithms [18]. Even within a single model, alternatives can also exist.…”
Section: Various Concepts Around Alternativesmentioning
confidence: 99%
See 3 more Smart Citations
“…Woodbury et al [44] define alternatives as "structurally different solutions to a design," while variations are "design solutions with identical model structure, but having different values assigned to parameters." Recent studies on data scientists' work practices have found that they write alternative versions of exploratory code [2,16,24,36] or use multiple alternative models, typically generated by different classes of 1 machine-learning algorithms [18]. Even within a single model, alternatives can also exist.…”
Section: Various Concepts Around Alternativesmentioning
confidence: 99%
“…Focusing on visual analytics systems, Chen [7] and Guenther [12] describe other types of alternatives, including data and visualization alternatives. Whereas many of those studies observe alternatives in specific contexts, such as design-space exploration and computational notebooks [16,24], our aim is to study the variety of alternatives that might exist in the wild and the processes around those alternatives.…”
Section: Various Concepts Around Alternativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there are several studies tackling usability, cognitive, and reproducibility aspects of computational notebooks. For instance, in reproducibility [36,47,48,58], education [44], exploratory programming [2,18,29,30], documentation [76], and data journalism [78]. However, no attention has been paid from the language engineering point of view.…”
Section: :21mentioning
confidence: 99%